Health inequalities in Germany and in international comparison: trends and developments over time - Thomas Lampert; Lars Eric Kroll; Benjamin Kuntz; Jens Hoebel (Journal of Health Monitoring, 2018)
Social epidemiological research has consistently demonstrated that people with a low socioeconomic status are particularly at risk of diseases, health complaints and functional limitations, and die at younger ages than those with a higher socioeconomic status. Greater stresses and strains in the workplace, family and living environment are under discussion as possible explanations. Health-related behaviours, psycho-social factors and personal resources, which are important in coping with everyday demands, certainly also play a role. From a public health and health policy perspective, reducing these health inequalities is an important goal. Insights into developments and trends in health inequalities over time can contribute towards highlighting new and emerging problems, and can thus help identify possible target groups and settings for relevant interventions. At the same time, these insights provide a basis upon which the success of policies and programmes that have already been implemented can be analysed and measured. Against this background, this review examines how health inequalities in Germany have developed over the last 20 to 30 years and places its findings within the context of the latest international research in this field.